Anatase TiO2 (101) and wurtzite ZnO (001) modified polymer for visible light-photocatalytic efficiency enhancement - Kantawong T. (2017)
© 2016 Taylor & Francis Group, LLC. Photocatalytic property of titanium dioxide and zinc oxide was used in several of application in the environmental field due to their high oxidation power and a self-sensitized degradation in a wide range of organic compound. Unfortunately, the large band gap of these metal oxides absorbs only UV radiation and limits the photocatalytic efficiency results in high cost of photocatalytic degradation of environmental pollutant. To be used under visible light irradiation, time-dependent density functional theory was applied to study anatase titanium dioxide (101) and wurtzite zinc oxide (001) with modified organic materials. Four modified structures, including polyisoprene ring, polyisoprene chain, polyacethylene, and polyphenylenevinylene, were investigated. The electronic structure and simulated UV-Vis spectra were analyzed.